SOCIETAL PEACE AND POSSESSION OF ARMS: A FIELD STUDY IN BAGHDAD - ISMAEL, AMEER; NAJIM, SAHAR (Al-Adab Journal, 2024)
The importance of carrying arms and its role in building societal peace is clarified by the attempt to identify the behaviour of this society and its impact on the cultural advancement of the community and the country alike.The study aims at exploring the role of carrying weapons in building societal peace, since carrying arms is a pivotal issue in the Iraqi society because of the spread of this phenomenon especially after the year 2003 and its aftermath which sometimes needs a long time to be reformed, hence, the study seeks the main reasons that caused the increase of this phenomenon and the way to decrease it.The study sheds light on analysing the dimensions which help building peace like security and human development, societal ladder development, eco-psychology,The study has followed the social survey approach in which the questionnaire tool is utilised, which consists of a (514 fe/males) who form the community of the study, from both parts of Baghdad Karkh and Rasafa, and then collecting data via the questionnaire form which consists of 50 specialized and essential questions.The findings confirmed that disorderly and unconditional arm carrying might increase the ratio of crime, violence, blackmail, threats in society and its effect on maintaining societal peace and cultural advancement to the community and country; in addition to the fact that it might lead to disintegration in social bonds, absence of trust among the community members on one hand, and the community and the law force on the other hand.